2012
DOI: 10.1160/th11-08-0556
|View full text |Cite
|
Sign up to set email alerts
|

Platelet soluble CD40L and matrix metalloproteinase 9 activity are proinflammatory mediators in Behçet disease patients

Abstract: Platelets are the major source of plasma-soluble CD40L (sCD40L), an important inflammatory mediator. This study explored the impact of platelet-derived sCD40L on Behçet disease (BD), an autoinflammatory vasculitis. We also searched for influences by platelet matrix metalloproteinases (MMP) -2 and MMP-9, implicated in several inflammatory diseases, on CD40L shedding from platelet membrane. Platelet activation were studied by flow cytometry and aggregometry, surface expression of CD40L and platelet-leukocyte agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 50 publications
1
8
2
Order By: Relevance
“…However, we did not find any differences in PTS between the patients and the controls. Although higher platelet activation and response to stimulus have been reported in BD patients [13,32], our research group recently published a study of platelet function in the same group of BD patients included in the present study and found no differences in platelet activation markers between the controls and the BD patients, either at baseline conditions or after stimulation with agonists (TRAP and ADP) [33]. After considering this finding and the lack of differences in PTS and platelet contribution to the ROTEM trace between the groups, we conclude that platelets are not the cause of the deviation in the ROTEM results.…”
Section: Discussionmentioning
confidence: 82%
“…However, we did not find any differences in PTS between the patients and the controls. Although higher platelet activation and response to stimulus have been reported in BD patients [13,32], our research group recently published a study of platelet function in the same group of BD patients included in the present study and found no differences in platelet activation markers between the controls and the BD patients, either at baseline conditions or after stimulation with agonists (TRAP and ADP) [33]. After considering this finding and the lack of differences in PTS and platelet contribution to the ROTEM trace between the groups, we conclude that platelets are not the cause of the deviation in the ROTEM results.…”
Section: Discussionmentioning
confidence: 82%
“…Here, MMP9 was involved in the shedding of CD40L after platelet-neutrophil interaction. Again, different experimental approaches confirmed a role for MMP9 [ 127 , 128 , 129 , 130 ].…”
Section: Platelets Cd40l and Molecular Signalingmentioning
confidence: 93%
“…CD40L protein expression was determined by flow cytometry as previously described [ 14 , 26 ]. Platelets were obtained and assessed by flow cytometry for CD40L protein expression before and after stimulation with 0.2 U/ml thrombin for 5 minutes at 37 °C in a 5% CO 2 atmosphere [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fernández-Bello et al [ 14 ] showed higher levels of plasma and platelet-derived sCD40L in a group of patients with BD, although no differences in platelet activation or platelet-leukocyte aggregate formation were observed. In normal mouse neutrophils, sCD40L strongly stimulates the oxidative burst via a CD40-dependent phosphoinositide 3-kinase/NF-κB pathway [ 15 ].…”
Section: Introductionmentioning
confidence: 99%